The Effect of Composition of Cocopeat Planting Media and Addition of Goat Manure Fertilizer on Gelinggang Microgreens (Cassia alata L.) - Tsalitsa Aghnia Nazhiifah; Ronny Mulyawan; Jumar; Irvan Indra Resnawan (Warmadewa University Press, 2025)
Microgreens are plants with a short duration of 7–14 days after germination. Microgreens are more commonly used as salads, but can also be used as a source of medicinal ingredients that are rich in antioxidants. Gelinggang plants are shrubs that are useful in traditional medicine because they can be used as antibiotics for several diseases. Determination of good planting media that supports the growth of microgreens and high chemical content is still being studied. The combination of cocopeat and goat manure composition is considered to be an option as a suitable medium for microgreens. This study aims to determine the effect of the composition of cocopeat and goat manure planting media on the growth of Gelinggang microgreens (Cassia alata L.). This study used a Completely Randomized Design (CRD) with one factor and five treatments, namely P0 (control, 150 g cocopeat), P1 (20% goat manure + 120 g cocopeat), P2 (25% goat manure + 112.5 g cocopeat), P3 (30% goat manure + 105 g cocopeat), and P4 (35% goat manure + 97.5 g cocopeat), with four replications. The parameters observed included plant height, fresh weight, and chlorophyll a, chlorophyll b, and total chlorophyll content. The results showed that the best treatment that was able to significantly increase plant height, fresh weight, and chlorophyll content was a combination of 20% goat manure and 120 g cocopeat, which was proven to be an alternative planting medium that supports optimal growth of Gelinggang microgreens plants.